A multi-port power conversion system for the more electric aircraft - Gu, Chunyang; Yan, Hao; Yang, Jiajun; Sala, Giacomo; De Gaetano, Daniele; Wang, Xuchen; Galassini, Alessandro; Degano, Michele; Zhang, Xin; Buticchi, Giampaolo (Institute of Electrical and Electronics Engineers Inc., 2020)
In more electric aircraft (MEA) weight reduction and energy efficiency constitute the key figures. Additionally, the safety and continuity of operation of its electrical power distribution system (EPDS) is of critical importance. These sets of desired features are in disagreement with each other, because higher redundancy, needed to guarantee the safety of operation, implies additional weight. In fact, EPDS is usually divided into isolated sections, which need to be sized for the worst-case scenario. Several concepts of EPDS have been investigated, aiming at enabling the power exchange among separate sections, which allows better optimization for power and weight of the whole system. In this paper, an approach based on the widespread use of multi-port power converters for both DC/DC and DC/AC stages is proposed. System integration of these two is proposed as a multiport power conversion system (MPCS), which allows a ring power distribution while galvanic isolation is still maintained, even in fault conditions. Thus, redundancy of MEA is established by no significant weight increase. A machine design analysis shows how the segmented machine could offer superior performance to the traditional one with same weight. Simulation and experimental verifications show the system feasibility in both normal and fault operations.